Open channel noise. III. High-resolution recordings show rapid current fluctuations in gramicidin A and four chemical analogues. - Sigworth, F J (1987)
Using a technique for high-resolution recording of currents from lipid bilayers, we have measured the current fluctuations in open channels formed by gramicidin A (GA) and the four analogues L-Ala7-GA, L-Leu5-GA, con D-Leu5a-L-Ala5b-GA and, des-L-Val7-D-Val8-GA. Over the frequency range 40 Hz-20 kHz the fluctuations in each type of channel showed flat (frequency independent) spectral densities which ranged from 1.1 to 2.4 times the value expected from shot noise. Larger values were obtained at 200 mV membrane potential than at 100 mV, and with 200 mM CsCl than with 1 M CsCl as the bath solution. A likely explanation for the excess noise would be the existence of brief interruptions in the channel current lasting less than 3 microseconds.